Studies on biodiesel production from Pongamia oil using heterogeneous catalyst and its effect on diesel engine performance and emission characteristics. Issue 4 (3rd July 2016) - Anjana, P.A.; Niju, S.; Begum, K.M. Meera Sheriffa; Anantharaman, N.; Anand, R.; Babu, D.
ABSTRACT: Commercial calcium oxide (CaO) impregnated with 25 wt% potassium iodide (KI) was prepared by wet impregnation method and adopted for transesterification of Pongamia oil using methanol. The synthesized catalyst (KI/CaO) was characterized using different techniques such as X-ray Diffraction, Fourier Transform Infrared Spectroscopy (FTIR), Brunauer-Emmett-Teller and Scanning Electron Microscopy analysis. Under the reaction conditions of 12:1 methanol:oil ratio, 4 wt% KI/CaO catalyst, 2 h reaction time and at a reaction temperature of 65°C, a maximum biodiesel conversion of 95.7% was obtained. Synthesized biodiesel was characterized by FTIR and H Nuclear Magnetic Resonance Spectroscopy techniques. The performance and emission characteristics of different blends of Pongamia biodiesel and conventional diesel were tested using a single-cylinder, four-stroke IC engine and the results were compared.